Beyond the “urge to move”: objective measures for the study of agency in the post-Libet era - Wolpe, Noham; Rowe, James B. (Frontiers in Human Neuroscience, 2014)
The investigation of human volition is a longstanding endeavour from both philosophers and researchers. Yet because of the major challenges associated with capturing voluntary movements in an ecologically relevant state in the research environment, it is only in recent years that human agency has grown as a field of cognitive neuroscience. In particular, the seminal work of Libet and colleagues in 1983 paved the way for a neuroscientific approach to agency. Over the past decade, new objective paradigms have been developed to study agency, drawing upon emerging concepts from cognitive and computational neuroscience. These include the chronometric approach of Libet’s study which is embedded in the ‘intentional binding’ paradigm, optimal motor control theory and most recent insights from active inference theory. Here we review these principal methods and their application to the study of agency in health and the insights gained from their application to neurological and psychiatric disorders. We show that the neuropsychological paradigms that are based upon these new approaches have key advantages over traditional experimental designs. We propose that these advantages, coupled with advances in neuroimaging, create a powerful set of tools for understanding human agency and its neurobiological basis.